Failure of Seattle and its implications (ECLAC Port of SpainTT, 2000)
Examines the evolution of the positions of developing countries on the General Agreement on Tariffs and Trade (GATT). Reviews recent trends in international trade, The Uruguay Round agreements and their implementation, emphasizing some of the issues of concern advanced by the members of the World Trade Organization (WTO), in particular the developing countries.
Bibliography: p. 13